Turtle in Paradise: The Graphic Novel - Jennifer L. Holm (Random House Graphic, 2021)
She's smart and tough and has seen enough of the world not to expect a Hollywood ending. After all, it's 1935 and jobs and money and sometimes even dreams are scarce. So when Turtle's mama gets a job housekeeping for a lady who doesn't like kids, Turtle says goodbye without a tear and heads off to Key West, Florida, to live with relatives she's never met. Florida's like nothing Turtle's ever seen before though. It's hot and strange, full of ragtag boy cousins, family secrets, scams, and even buried pirate treasure! Before she knows what's happened, Turtle finds herself coming out of the shell she's spent her life building, and as she does, her world opens up in the most unexpected ways. Filled with adventure, humor and heart, Turtle in Paradise is an instant classic both boys and girls will love.
Keywords: Graphic Novel -- Graphic Novel